Development and validation of the core life activities scale - Cho, Surin; Park, Kiho; Jung, Dawoon; Son, Gaeun; Cho, Eunsil; Choi, Kee-Hong (Frontiers in Psychology, 2024)
Life activities profoundly influence well-being, mental health, and quality of life. The COVID-19 pandemic has heightened the importance of monitoring these activities for psychological and emotional health. However, existing measurement tools are limited, particularly for assessing psychological health. To address this gap, we developed and validated the Core Life Activities (CORE) scale, comprising five key factors (sleep, exercise, learning, diet, and social relationships) identified in neuroscience, cognitive psychology, and gerontology. In Study 1 (n = 1,137), exploratory and confirmatory factor analyses supported a single-factor structure with good model fit (χ² = 6.377, df = 3, TLI = 0.992, CFI = 0.998, RMSEA = 0.031), demonstrating robust internal consistency (Cronbach's alpha = 0.776) and test-retest reliability (intraclass correlation coefficient = 0.522, p < 0.001). The CORE exhibited significant convergent validity with mental health screening tools for depressive and anxiety disorders and suicidality. Study 2 (n = 684) confirmed a significant correlation between CORE and the World Health Organisation Quality of Life Brief Version, complementing the convergent validity found in Study 1. In addition, discriminant validity was confirmed by a non-significant correlation with the COVID-19 Preventive Behavior Scale. The findings establish the CORE as a reliable and valid tool, offering a simple yet comprehensive measure for assessing core life activities with potential applications in diverse environments.